Analysis of Generation Z Consumer Behavior in the Food and Beverage Industry in Indonesia: The Influence of Product Personalization, Social Media Engagement, and Brand Experience - Suryaningrum, Dyah Ayu; Utami, Eva Yuniarti; Lusianawati, Hayu; Thalib, Najdah (Westscience Press, 2023)
In the Indonesian food and beverage sector, this study examines how brand experience, social media interaction, and product customisation affect Generation Z customer behavior. Data gathered from 150 Generation Z customers was analyzed using a quantitative method that made use of structural equation modeling with partial least squares (SEM-PLS). The results of the study show a strong positive correlation between the behavior of Generation Z consumers and each independent variable, including social media participation, brand experience, and product customisation. The findings highlight how crucial strategic customisation, a strong social media presence, and improved brand experiences are in influencing Generation Z customers' preferences and decisions. These observations have important ramifications for companies who want to modify their marketing plans in order to successfully connect this ever-changing group of consumers in the Indonesian market.